Computational methods for design and synthesis of planar mechanisms - Pucheta, Martín Alejo (2009)
Fil: Pucheta, Martín Alejo. Universidad Nacional del Litoral. Facultad de Ingeniería y Ciencias Hídricas; Argentina.